Corporate site selection and economic development : a 30-year perspective - Williams, Mark L. ([Place of publication not identifed] : [publisher not identified], 2021)
Mark Williams provides a truly informed and unique perspective based on his 30 years in corporate site selection and state level economic development. The book not only highlights the best site selection and economic development practices but also describes the high cost of mistakes, particularly when the wrong choice is made for corporate facility locations. A particular focus is the future of site selection moving out of the COVID-19 pandemic.
Preface -- Introduction -- Part 1. Economic Development -- Part 2. Site Selection -- Acknowledgements -- Glossary of Terms -- Appendix I. -- About the author.
Corporate site selection and economic development :, Corporate
Keywords: ECONOMIC DEVELOPMENT